2007
DOI: 10.1002/adma.200602457
|View full text |Cite
|
Sign up to set email alerts
|

New Transparent Methylsilsesquioxane Aerogels and Xerogels with Improved Mechanical Properties

Abstract: Since they were first prepared in 1931 via supercritical drying (SCD), [1] aerogels have been utilized for rather specific applications in spite of their wide range of extraordinary properties, such as high optical transparency (> 90 %), large surface areas (ca. 1000 m 2 g -1 ), low refractive indices (< 1.01), high thermal and acoustic insulation values, and low dielectric constants (ca. 1.1). An aerogel-based Cherenkov detector has been used to detect charged elementary particles, thus contributing to the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
310
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(327 citation statements)
references
References 31 publications
13
310
1
3
Order By: Relevance
“…[1][2][3][4] In particular, the optical transparency of silica aerogel in the solar spectrum is crucial for many solar related applications [5][6][7][8] and has been studied extensively. [9][10][11][12][13][14][15][16][17][18] J. Fricke et al showed that the optical transparency of silica aerogels is tied closely to its microstructure which acts as Rayleigh scattering centers.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In particular, the optical transparency of silica aerogel in the solar spectrum is crucial for many solar related applications [5][6][7][8] and has been studied extensively. [9][10][11][12][13][14][15][16][17][18] J. Fricke et al showed that the optical transparency of silica aerogels is tied closely to its microstructure which acts as Rayleigh scattering centers.…”
Section: Introductionmentioning
confidence: 99%
“…14), 15) A modified 2-step acid/base sol-gel process utilizing hydrolysis of urea enhances the homogeneous gelation of MTMS. Additionally, an adequate surfactant is employed to suppress macroscopic phase separation which otherwise would develop in the micrometer scale and eliminate transparency.…”
Section: )-6)mentioning
confidence: 99%
“…With appropriate surfactant, such as n-hexadecyltrimethylammonium salt (CTAB for bromide or CTAC for chloride) or poly(ethylene oxide)-block-poly(propylene oxide)-block-poly(ethylene oxide) triblock copolymers, phase separation is effectively suppressed and transparent aerogels can be obtained. 20) The PMSQ aerogels obtained after supercritical drying exhibit similar properties to the carefully-prepared conventional silica aerogels such as low density (<0.15 g cm ¹3 ) and high porosity (³90%), and high visible-light transparency (³90% at 550 nm through a 10 mm-thick-equivalent sample). 20) 22) The typical PMSQ aerogels prepared with CTAB consist of a well-defined mesoscopic pore structure with 30 50 nm pores and solid frameworks formed by nano particles (³10 nm in diameter).…”
Section: Preparationmentioning
confidence: 94%
“…20) The PMSQ aerogels obtained after supercritical drying exhibit similar properties to the carefully-prepared conventional silica aerogels such as low density (<0.15 g cm ¹3 ) and high porosity (³90%), and high visible-light transparency (³90% at 550 nm through a 10 mm-thick-equivalent sample). 20) 22) The typical PMSQ aerogels prepared with CTAB consist of a well-defined mesoscopic pore structure with 30 50 nm pores and solid frameworks formed by nano particles (³10 nm in diameter). Owing to the methyl groups, the PMSQ aerogels naturally exhibit hydrophobicity without the surface modification.…”
Section: Preparationmentioning
confidence: 94%